2015
DOI: 10.1186/s12905-015-0223-0
|View full text |Cite
|
Sign up to set email alerts
|

Does obesity have detrimental effects on IVF treatment outcomes?

Abstract: BackgroundThe aim of this study was to investigate the influence of body mass index (BMI) on the in vitro fertilization (IVF) treatment outcomes in a cohort of women undergoing their first IVF, using an intracytoplasmic sperm injection (ICSI).MethodsThis retrospective cohort study included 298 cycles from women younger than 38 years old undergoing IVF-ICSI at a university infertility clinic. The treatment cycles were divided into three groups according to the BMI of the women involved: normal weight (18.5 ≤ BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 22 publications
9
35
1
8
Order By: Relevance
“…In the setting of IVF, increased doses of gonadotropin for inducing ovulation or stimulating the ovaries to obtain mature oocytes were required in obese women [6,13]. Impaired ovarian responsiveness to gonadotropin stimulation and reduced number of oocytes retrieved were reported to be associated with obesity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of IVF, increased doses of gonadotropin for inducing ovulation or stimulating the ovaries to obtain mature oocytes were required in obese women [6,13]. Impaired ovarian responsiveness to gonadotropin stimulation and reduced number of oocytes retrieved were reported to be associated with obesity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that women with BMI more than 35 kg/m2 are at high risk during ART [17] . Therefore, many prior studies have investigated the impact of raised BMI on the pregnancy outcomes of IVF/ICSI but with disparate results [23] . Some studies conducted on the patients undergoing IVF/ICSI using DE reported the negative impact of BMI, whereas others reported no difference in the reproductive outcomes in obese and normal DE recipients [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that the pregnancy outcome followed by ART is not influenced by BMI. However, they might require a high dose of gonadotropin and a longer period of stimulation [23,31] .…”
Section: Discussionmentioning
confidence: 99%
“…Although infertility associated with obesity has been related to anovulation [7], data have shown that the time to spontaneous pregnancy is significantly longer in obese women even in those who have regular menstrual cycles [10][11]. Despite data pertaining to obesity and IVF success from individual centers is controversial [101][102][103], data from large national studies showed that, obese women undergoing COH with oocyte retrieval for IVF have significantly worse outcomes compared to normal-weight women [104][105].…”
Section: Controlled Ovarian Hyperstimulation In Obese Women and The Amentioning
confidence: 99%